How to lead world society towards sustainable development? - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
In political terms it all started with the World Commission on Environment and Development which in its 1987 report Our Common Future stated that ...humanity has the ability to make development sustainable - to ensure that it meets the needs of the present without compromising the ability of future generations to meet their own needs (WCED, p. 8). The Commission defined sustainable development as ... a process of change in which the exploitation of resources, the direction of investment, the orientation of technological development, and institutional change are made consistent with future as well as present needs (WCED, p. 9; italics added), Sustainable development thus deals with two fundamental issues, i.e. inter-generational equity and comprehensive structural adjustment.
Keywords: 300; Nachhaltige Entwicklung; Umweltpolitik; Strukturwandel; Ressourcenökonomik; Energiesparen; Wirtschaftlic